EFFECT OF MEDIATION WORK ENGAGEMENT TO LEADER MEMBER EXCHANGE AND JOB INSECURITY ON INNOVATIVE WORK BEHAVIOR - Kurniawan, Raden Aldino; Ranihusna, Desti (Universitas Negeri Semarang, 2019)
The purpose of this research is to test the effect of leader-member exchange, job insecurity on innovative work behavior through work engagement CV. Laksana employee. The sampling method used nonprobability sampling with incidental technique and sample 109 employees. The data analysis in this research used a descriptive statistical test method, derivative tests including validity and reliability, and hypothesis testing. The tool used to test in this research used SmartPLS 3.0. The result of this research show leader-member exchange positively relates to innovative work behavior. However, job insecurity does not have a relationship with innovative work behavior. Leader-member exchange and job insecurity relate to work engagement. Work engagement can mediate leader-member exchange and job insecurity to innovative work behavior. The conclusion of this research is the higher level of leader-member exchange in the work environment can maximalized employee innovative work behavior. The higher level of job insecurity can minimize employee work engagement. Suggestion for future research is to try another variable that can be used to enhance employee innovative work behavior.